The Effect of Inflation Rate and Foreign Exchange on Company Value at Bank Mandiri Tbk - Yusnaini Yusnaini (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2023)
The global economic crisis in 2008 still has an impact on the Indonesian capital market. The impact of the crisis was reflected in the correction of stock prices by 40-60 percent from the initial position in 2008. Two of the main impacts of stock price fluctuations in the capital market due to the global economic crisis in 2008 were the inflation rate and volatile foreign exchange rates. The research method used is the ex post facto method. Data collection is done by recording observations, interviews, and literature research. The hypothesis is that there is an influence of the inflation rate and foreign exchange rates on the value of the company PT Bank Mandiri (Persero) Tbk. The analysis is in the form of simple and multiple linear regression analysis, correlation coefficient analysis, coefficient of determination analysis, and hypothesis testing. The result is that there is a moderate relationship with a positive correlation between the inflation rate and foreign exchange rates on the value of the company with a correlation value (R) of 0.595 and linear regression analysis with the equation Y = 319.972 + 71.431X1 + 0.843X2 besides that obtained Kd of 0.354 and distribution Fhitung 15.639 > Ftabel 3.162 means Ho is rejected and Ha has accepted means that overall the inflation rate and foreign exchange rates together affect the value of the company at PT. Bank Mandiri (Persero) Tbk